Different responses of growth and physiology to warming and reduced precipitation of two co-existing seedlings in a temperate secondary forest - Yuan, Junfeng; Yan, Qiaoling; Wang, Jing; Xie, Jin; Li, Rong (Frontiers in Plant Science, 2022)
Warming and precipitation reduction have been concurrent throughout this century in most temperate regions (e.g., Northeast China), which have increased drought risk to the growth, migration, or mortality of tree seedlings. Coexisting tree species with different functional traits in temperate forests may have inconsistent responses to both warming and decreased precipitation, which could result in the species distribution shift and community dynamics. Unfortunately, little is known about the growth and physiology responses of coexisting species to the changes of these two meteorological elements. We selected two coexisting species in a temperate secondary forest of Northeast China: Quercus mongolica Fischer ex Ledebour (drought-tolerant species) and Fraxinus mandschurica Rupr. (drought-intolerant species), and performed an experiment under strictly controlled conditions simulating predicted warming (+2 ℃, +4 ℃) and precipitation reduction (-30%) compared with current conditions and analyzed the growth and physiology of seedlings. The results showed that compared with control, warming (including +2 ℃ and +4 ℃) promoted the specific area weight and total biomass of F. mandschurica seedlings, which were caused by the increases in foliar N content, the activity of PSII reaction center, and chlorophyll content. +2 ℃ plus reduced precipitation enhanced root biomass of Q. mongolica, resulting from root length increase. To absorb water in drier soil, seedlings of both species had more negative water potential under the interaction between +4 ℃ and precipitation reduction. Our results demonstrate that drought-tolerant species like Q. mongolica will adapt to the future drier conditions with the co-occurrence of warming and precipitation reduction, while drought-intolerant species will accommodate to warmer environments.